Psychological Features of the Arabs - E N Reznikov (Peoples' Friendship University of Russia (RUDN University), 2008)
One of the new directions of the development of the educational process in RPFU can be the working out and practical application of the results of the research on the problem of adaptation of foreign students at the university taking into account their ethno-psychological features. Taking this into consideration we are planning to publish a number of articles on ethno-psychological features of foreign students and the program of their psychological adaptation. Of all the countries of Asia we shall consider the psychological features of the Arabs and the Chinese as the majority of students that come to study in RPFU are from these countries. The submitted article analyses the psychological features of the Arabian ethnos and the factors it was generated by.